2021
DOI: 10.3389/fcell.2021.729965
|View full text |Cite
|
Sign up to set email alerts
|

HIF1α Regulates IL17 Signaling Pathway Influencing Sensitivity of Taxane-Based Chemotherapy for Breast Cancer

Abstract: Hypoxia-induced chemotherapy resistance is the main hindrance for solid tumor treatment. Hypoxia inducible factor-1α (HIF1α), an adaptive gene of hypoxia condition, played an important role in affecting chemotherapy sensitivity for many cancer types and various therapeutic regimens. This study focused on the impact of HIF1α on predicting response and survival of taxane-based neoadjuvant therapy (NAT) for breast cancer (BC) patients and the concrete mechanism that HIF1α mediated paclitaxel chemo-insensitivity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…For example, changes in gene expression levels and DNA methylation silencing key genes can inhibit related signaling pathways, leading to drug resistance in BC (21,22). There is much evidence to show (28). The results of our study also revealed that CXCL10 is highly expressed in pCR patients, indicating that a higher expression level of CXCL10 may result in pCR in BC patients.…”
Section: Discussionsupporting
confidence: 54%
“…For example, changes in gene expression levels and DNA methylation silencing key genes can inhibit related signaling pathways, leading to drug resistance in BC (21,22). There is much evidence to show (28). The results of our study also revealed that CXCL10 is highly expressed in pCR patients, indicating that a higher expression level of CXCL10 may result in pCR in BC patients.…”
Section: Discussionsupporting
confidence: 54%
“…Intracellular response to hypoxia is mainly mediated by Hypoxia-inducible factors-1α and -2α (HIF-1α and HIF-2α). Our previously study proved that HIF-1α expression is reversely associated with paclitaxel-based NAC response and HIF-1α could lead to paclitaxel chemoresistance in vitro experiments [27].Therefore, we postulate that HIF-1α might possibly drive Lin01436 expression. Jiao et al reported that Linc01436 could upregulate the expression of MAPK1,Which is known as ERK2, a member of the Ras/Raf/ERK signaling pathway [28].…”
Section: Discussionmentioning
confidence: 80%
“…Results from KEGG functional enrichment analysis revealed a close association between the IL-17 signaling pathway and the progression of BRCA. It was also observed that HIF1α could influence the sensitivity of patients toward paclitaxel chemotherapy by regulating the IL17 signaling pathway 36 . Enhanced PD-1/PD-L1 expression was associated with the upregulation of the IL-17 signaling pathway-related genes, and the improved IL-17 signaling was found to be associated with the elevated extents of CD8+ T cell infiltration and changes in TME in patients with BRCA 37 .…”
Section: Discussionmentioning
confidence: 99%